PENGGUNAAN MODEL JIGSAW UNTUK MENINGKATKAN MOTIVASI BELAJAR SISWA PADA MATA PELAJARAN IPS DI KELAS VIII.A SMPN 1 BANGKO PUSAKO TAHUN PELAJARAN 2015/2016 - ', Mardianto; ', Gusnardi; ', R.M Riadi (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2016)
Abstract: This study entitled "Using Jigsaw Model to Improve Student Motivation in the IPS Lesson in Class VIII. A SMPN 1 Bangko Pusako Academic Year 2015/2016 ".This research was a classroom action research (PTK) collaboration between teacher and student with a number of students as subjects of research that as many as 30 people in the class VIII.A the school year 2015/2016. While the object is the use of cooperative learning model Jigsaw. Based on the results of the discussion and analysis set out in chapter IV can be concluded that use of the Jigsaw model can increase student motivation in social studies class VIII.A SMPN 1 Bangko Pusako the academic year 2015/2016. It can be seen from a spike of each meeting in each cycle. Special to IPS students' motivation to learn at the first meeting I cycle skor119 with the percentage of total 49.5% with medium category. The results of the second meeting of the first cycle, a total score of 139 with a percentage of 57.9% with a high category. The meeting I cycle II total score of 156 with a percentage of 65% with a high category. Second meeting of the second cycle a total score of 177 with a percentage of 73.75% with a high category. So based on that increase occurring in each cycle until reaching / exceeding the completeness criteria research, this study was successful / completed.Keywords: Jigsaw and Motivation